Social Unrest in the Wake of IMF Structural Adjustment Programs - Caleb Stroup; Benjamin Zissimos (Center for Economic Studies and ifo Institute (CESifo), 2013)
This paper proposes an answer to the question of why social unrest sometimes occurs in the wake of an IMF Structural Adjustment Program (SAP). Under certain circumstances, partly determined by a country's comparative advantage, a nation's elite may have an incentive to make transfers to the rest of society through government employment in order to quell social unrest. But under an SAP, the elite are constrained from making such transfers and consequently social unrest may arise. The paper proposes a framework from which a prediction can be made about the circumstances under which social unrest can be expected to occur. It then takes this prediction to the data and finds empirical support for it.
Keywords: D30; D74; F10; O12; P14; 330; institutions; International Monetary Fund (IMF); social unrest; structural adjustment; trade integration